A new variety of medical case reporting as a tool in ESP teaching as well as in medical training and professional development - Żelazowska-Sobczyk, Magda; Zabielska, Magdalena (Glottodidactica, 2017)
In this paper, a new generic development in the medical case report will be presented as a potential tool in a variety of medical contexts. A case report describes new diseases or their novel aspects, and its new interactive type additionally allows readers to comment on published cases and features patients’ first person narratives. This development may be a useful tool in medical English language courses, in medical training as well as in professional development. This way the paper systematises the knowledge on the application of medical case reports in general and re-evaluates their potential in strictly medical contexts